2016
DOI: 10.1088/0957-4484/27/20/205705
|View full text |Cite
|
Sign up to set email alerts
|

Making consistent contacts to graphene: effect of architecture and growth induced defects

Abstract: The effect of contact architecture, graphene defect density and metal-semiconductor work function difference on resistivity of metal-graphene contacts have been investigated. An architecture with metal on the bottom of graphene is found to yield resistivities that are lower, by a factor of 4, and most consistent as compared to metal on top of graphene. Growth defects in graphene film were found to further reduce resistivity by a factor of 2. Using a combination of method and metal used, the contact resistivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…9). reported that also growth defects may reduce the contact resistivity by a factor of two [118]. Indeed, the contact resistivity for Pt, Au and Pd, obtained at carrier concentration varying from −1.5 to +1.5 × 10 12 cm −2 , have been measured for two different defect densities, showing that for each metal, the graphene with higher defect density has a lower resistivity.…”
Section: Refined Fabrication Processmentioning
confidence: 93%
See 1 more Smart Citation
“…9). reported that also growth defects may reduce the contact resistivity by a factor of two [118]. Indeed, the contact resistivity for Pt, Au and Pd, obtained at carrier concentration varying from −1.5 to +1.5 × 10 12 cm −2 , have been measured for two different defect densities, showing that for each metal, the graphene with higher defect density has a lower resistivity.…”
Section: Refined Fabrication Processmentioning
confidence: 93%
“…A way to improve the contact resistance is using a suitable device architecture. With respect the standard configuration, in which the metal is deposited on top of graphene layer, it has been shown that by realizing a "metal-on-bottom" configuration [118], the contact resistance may be improved.…”
Section: Refined Fabrication Processmentioning
confidence: 99%
“…However, although contact resistance is an important obstacle for further improvement, which is still not well understood. Conventional deposition of metal electrodes on top of the graphene surface often resulted in a large contact resistance [5,6,7]. In order to modify the Fermi level difference between metal and graphene to improve the metal/graphene (M/G) interface, distinct metals with different work functions were initially attempted [8].…”
Section: Introductionmentioning
confidence: 99%
“…A worth-noting point observed in our samples is that the I D peak intensity, which is also connected with defects, is on a higher side but these defects are advantageous with respect to contact resistance on metals4243, and thus will be beneficial for ULSI Interconnects’ applications.…”
Section: Discussionmentioning
confidence: 68%